Is young athletes bullying behaviour different in team, combat or individual sports? - Marracho, Philippe (2021)
This study aims at describing and comparing the prevalence of bullying behaviours and the perspective of victims, bystanders, and aggressors in team, individual, and combat sports. The survey involved 664 athletes of both genders (13–18 years old) from sports school and federated of several sports (team n= 451, individual n= 173, combat n= 40), who filled in the Prevention of Violence in Sport Questionnaire. The prevalence of bullying (victims, bullies, and bystanders) was 26.7% in team sports; 19.1% in individual sports, and 23.1% in combat. Through the Chi-square test, it was verified that there were no significant differences between different sports in what concerns the prevalence of bullying behaviours; neither was there a difference in the perspective of victims, bystanders, and aggressors. The percentage was bigger in victims (7.7%) and bystanders (17.4%) in combat sports, and aggressors (3.3%) in team sports. There are not aggressors in combat sports. Further studies are needed in order to achieve a deeper knowledge of the problem and plan strategies to prevent this sort of behaviour